La bio-indication de la pollution aquatique par les microalgues (Cas de l'Oued "Bounamoussa" et du Lac des" Oiseaux" - Necib, A; Rezig, H; Boughedir, L. (My University, 2013)
Continental aquatic environments are complex, fragile and governed by specific physico- chemical ecosystems laws. Microalgae that colonize living precariously and totally dependent. The most tolerant genera adapt to the input of an exogenous substance or a change in physico-chemical parameters. We used microalgae as biological indicators of water pollution in two sites: Bounamoussa's River and Lake of the Birds (W.Tarf). The method applied is the index of organic pollution recommended by Palmer (1969), which is to translate the level of contamination in water samples. The observation of morphological characteristics of collected microalgae allowed us to identify 20 genera. We recorded 10 genera in Bounamoussa's River: Microcystis, Euglena, Lepocinclis, Gomphonema, Melosira, Navicula, Synedra, Chlorella, Closterium and Scenedesmus. At the Lake of the Birds, we noted the existence of 17 genera: Aphanizomenon, Anabaena, Cylindrospermum, Merismopedia, Microcystis, Phormidium, Synechocystis, Phacus, Cyclotella, Gomphonema, Navicula, Synedra, Ankistrodesmus, Chlorella, Closterium, Pediastrum and Scenedesmus. The results show that the highest algal densities are recorded in the Lake of the Birds, followed by the Bounamoussa's River. According to the pollution index Palmer (1969), we found that there is little organic pollution (index = 9) at Bounamoussa's River. However, the contamination at the site of the Lake of the Birds by organic matter is considered average (index= 12). Keywords: Organic pollution -Microalgae - Bioindication -Pollution tolerant genera of algae -Palmer index (1969).